Cardiovascular and Renal Links along the Cardiorenal Continuum - José A. García-Donaire; Luis M. Ruilope (International Journal of Nephrology)
The cardiorenal syndrome includes the widely known relationship between kidney function and cardiovascular disease. A large number of patients have various degrees of heart and kidney dysfunction worldwide, both in developed and developing countries. Disorders affecting one of them mostly involve the other. Such interactions represent the pathogenesis for a clinical condition called cardiorenal syndrome. Renal and cardiovascular disease shares similar etiologic risk factors. The majority of vascular events are caused by accelerated atherosclerosis. Moreover, cardiovascular events rarely occur in patients without underlying disease; rather, they typically take place as the final stage of a pathophysiological process that results in progressive vascular damage, including vital organ damage, specifically the kidney and the heart if these factors are uncontrolled. Chronic kidney disease is a novel risk factor included at this stage that accelerates both vascular and cardiac damage.